A re-examination of China's share issue privatization - JIANG, Guohua (Institutional Knowledge at Singapore Management University, 2009)
Previous studies show that in contrast to evidence that share issue privatization (SIP) in most other countries have improved firm profitability, China's SIP of the 1990s had no such effect. We argue that the main reason for the failure of China's SIP is likely to have been the weak institutional environment in place at that time. We examine China's SIP in a more recent period in which the institutional environment was greatly improved. Using a matching sample method, we find that SIP firms continued to experience negative post-SIP profitability changes in our sample period. However, their performance decline was significantly less than that of their matched non-SIP SOEs. We also find that the introduction of the independent director rule helped to improve firm performance. Our results reconcile the findings of the SIP effect in China with international evidence and illustrate the importance of a developed capital market to ensuring the success of privatization schemes.